GREEN INFORMATION TECHNOLOGY READINESS MODEL USING FACTOR ANALYSIS METHOD IN INDONESIA - Sardjono, Wahyu; Perdana, Widhilaga Gia (Bina Nusantara University, 2019)
Green information technology has been increasingly becoming a strategic consideration for developing sustainable business practices through balancing economic and environmental performance of an organization. To help individual organizations better pursue green information technology, this paper presents a factor analysis based decision model for evaluating the green information technology readiness of an organization. The decision model effectively considers the multi-dimensional nature of the evaluation problem and appropriately handle the subjectivity and imprecision of the human evaluation process. An example is given for demonstrating the applicability of the model for evaluating the green information technology readiness of organization. Green information technology readiness is considered to be an organization?s capability to embed sustainability in the beliefs and attitudes in the development, deployment and disposal of information technology technical assets and in their information technology processes, practices and policies and in the governance systems to ensure compliance with internal and external sustainability expectations.